PROBLEMS OF INTERACTION BETWEEN TRADITIONAL AND MODERN ARCHITECTURAL FORMS - Arpine Sarkisovna Torosyan; Renata Ivanovna Kyulbakova (Современная наука и инновации)
The article considers the actual issue of the interaction of historical buildings in the Pyatigorsk with the conceptual architecture of the new buildings. In each city, this problem is solved differently, depending on various factors, including urban policy. Various social processes accelerate the pace of life is thus pushing for the need to introduce new tools of shaping. The author ^ found the logic of the development of architecture as historical and social phenomena. Monuments must be silent symbols of time and of the cultural heritage of civilization regardless of their stylistic orientation. The article also discusses how the location of new plants in the historical development and identifies the negative and positive moments in the planning of the city. The interaction of old and new architecture in a dynamic landscape environment.